The Influence of Transformational Leadership on Employee Engagement : The Role of Job Satisfaction as Mediating - Zufrie; Rizki Syahputra; Alwi Muhammad Adam; Fadzil Hanafi Asnora; Aulia Indra (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aims to determine the effect of transformational leadership on employee engagement by mediating job satisfaction. The research was conducted with a quantitative approach. The data analysis technique used is Structural Equation Modeling (SEM). The research was conducted on the employees of the culinary business in Rantauprapat. 210 questionnaires were distributed and 159 returned. Therefore, the sample in this study was as many as 159 people. The results showed that there was a positive and significant influence between transformational leadership on job satisfaction, there was a positive and significant influence between transformational leadership on employee engagement, and job satisfaction had a positive and significant effect on employee engagement. The results also showed that job satisfaction had an indirect effect on employee engagement. Keywords: transformational leadership, job satisfaction, employee engagement